2018
DOI: 10.1002/hfm.20776
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of just‐in‐time on sociotechnical practices' effect over quality and workers' health

Abstract: Sociotechnical (ST) theory emphasizes the notion that the design and performance of new systems can be improved, and can only work satisfactorily within an organization if the social and the technical aspects are brought together and treated as interdependent aspects of a work system. The implementation of lean manufacturing (LM) principles and practices has become popular, despite increasing demand on the current and emerging workforce to achieve higher levels of quality and flexibility with lower costs. Expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…In the social aspect, EMP is a vital human resource practice that offers direct forms of employee involvement in decision-making and emphasizes the principles of job enrichment and skill enhancement (Fernandez and Moldogaziev, 2011; Tortorella et al , 2019). Empowered employees have analytical, technical and problem-solving skills to handle unforeseen challenges of supplier JIT that undermine flexibility performance (Alcaraz et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the social aspect, EMP is a vital human resource practice that offers direct forms of employee involvement in decision-making and emphasizes the principles of job enrichment and skill enhancement (Fernandez and Moldogaziev, 2011; Tortorella et al , 2019). Empowered employees have analytical, technical and problem-solving skills to handle unforeseen challenges of supplier JIT that undermine flexibility performance (Alcaraz et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ghobakhloo and Azar (2018) suggest that AMT is the most current technology adopted in manufacturing operations subdivided into three dimensions: design and manufacturing technologies, process shop floor technologies and information, control and planning technologies. Existing studies have indicated that the use of AMT has a positive effect on flexibility performance because it facilitates the ability to respond quickly to customer requirements (Khanchanapong et al , 2014; Tortorella et al , 2019). Specifically, design-related AMT eases the difficulty of developing product configurations in response to different customer demands, thereby reducing design cycle time (Deshpande, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In evaluating employees workload during the design of a new workplace or iteration of an existing one, issues such as bottlenecks and overburden might emerge (Feitelson, 2015). As employees are a central part of socio-technical systems, it is necessary to address those issues to enhance their working conditions and efficiency (Tortorella et al, 2017(Tortorella et al, , 2019.…”
Section: Workload Assessmentmentioning
confidence: 99%
“…Similarly, Hines et al (2004) argued that there has been a significant development and evolution of the comprehension of LP concepts among organizations and researchers, varying in terms of focus, application and contexts. Such evolution has been possible due to an increasing set of practical and theoretical experiences of LP implementation across different areas and industry sectors, allowing to enhance the body of knowledge on LP and better shaping its concepts among researchers and practitioners (Paez et al, 2005;Holweg, 2007;Jayaraman et al, 2012;Tortorella et al, 2019).…”
Section: Lp Implementation Experiencementioning
confidence: 99%